Hypercholesterolemia-Induced Long-Term Increase of Macrophages in the Myocardium of New Zealand White Rabbits - Kinscherf, Ralf; Kamencic, Huse; Deigner, Hans-Peter; Metz, Jürgen (Cells tissues organs, 2003)
The effect of hypercholesterolemia on the number, immunological phenotype and oxidative stress-dependent processes of macrophages (MΦ) and dendritic cells (DC) was studied in New Zealand White rabbits
Gesehen am 19.10.2017